Shifting towards a consumer-centered economy and the implications for international trade - Matthias Helble (Asian Development Bank Institute (ADBI), 2018)
Globalization has radically changed the way in how goods and services are produced. The impact of globalization on production has been driven mainly by two determinants: In a first phase, a quick fall in transportation costs between countries and in a second, more recent phase, a drastic lowering of international communications costs. In this paper we argue that we are currently witnessing the start of another epochal change. Advances in communication and information technology enable companies to have more and more knowledge about the individual consumer. As a consequence, products and services can be marketed more specifically or can be customized according to the preference of the consumer. We call this new era the consumer-centered economy. The consumer-centered economy is challenging our standard trade and development theories in which consumers are typically assumed to be identical. We predict that the success of countries and firms will depend on how well they are able to integrate consumer information into the process of value addition. Producing standardized goods and services will offer little perspectives for economic development, even when integrated into regional value chains.
Keywords: F14; 330; international trade; trade costs; production networks; consumer; customization